PRINS and In Situ PCR Protocols - Pellestor, Franck.; Pellestor, Franck. (Methods in Molecular Biology,, 2006)
Carrying on the high standards of the much-praised first edition, leading researchers and clinical investigators have completely revised and updated PRINS and In Situ PCR Protocols to take advantage of the many new developments and applications that have occurred for cellular and molecular investigations. The authors contribute proven protocols for many variations of PRINS and in situ PCR, including a new, fast multicolor PRINS method for identifying human chromosomes, PRINS protocols for in situ detection of unique sequences and point mutations, a new dideoxy PRINS procedure, and in situ PCR and PRINS protocols for plants. They describe, in detail, various applications of PRINS in human cells (detection of gene deletions in cancer, detection of fetal cells in maternal blood, and assessment of aneuploidy in brain tissues and embryos) as well as in plant cells. Readily reproducible in situ PCR techniques are also presented for the detection of cytomegalovirus and for use in combination with microdissection. In situ RT-PCR techniques are also given for use in plant or cancer investigation. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and highly practical, PRINS and In Situ PCR Protocols offers molecular biologists, cytogeneticists, and cytologists a cutting-edge guide to today's new in situ labeling technology.